How Do Household Financial Obligations Impact the Equity Premium ? - Jahangiry, Pedram (Journal of Accounting and Finance, 2020)
In this paper, two specific channels are proposed to investigate how household financial obligations impact the equity premium. Preference channel and borrowing constraints channel. Preferences are defined over households’ consumption relative to their financial obligations. The model also introduces dynamic borrowing constraints, using financial obligation ratio as a proxy. A novel feature of the model is that in states of high marginal utility, the borrowing constraint binds and making it more difficult for households to smooth consumption. In addition, in these states, households become more risk averse. This dual mechanism both amplifies the risk premia and makes it time varying.